Penerapan Rapid Application Development (RAD) Dalam Pengembangan Aplikasi Penjualan Ikan Cupang Hias Berbasis Web - Septian Muhammad Fauzi; Mohammad Iwan Wahyuddin (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Betta.dja is a small business that sells ornamental betta fish located in Perum. Depok Jaya Agung, Jl. Apple 8, Ex. Rangapan Jaya, Depok City, in this transaction, usually Betta.Dja does COD (Cash On Delivery) for customers who want to buy fish on social media, or come directly to the store, because they do not have a sales website to provide information to customers. At this time Betta.dja recapitulates the sale of ornamental betta fish using only Microsoft Office. Because it is very inefficient in managing data. If any processed data is lost or damaged, it can result in inaccurate data. The application for selling ornamental betta fish uses a web-based RAD (Rapid Application Development) method. In this study, the expected result is an ornamental betta fish website by providing fast and accurate information.